Diagnosing Nodular Regenerative Hyperplasia of the Liver Is Thwarted by Low Interobserver Agreement - Jharap, Bindia (PLoS One, 2015)
BACKGROUND AND AIMS: Nodular regenerative hyperplasia (NRH) of the liver is associated with several diseases and drugs. Clinical symptoms of NRH may vary from absence of symptoms to full-blown (non-cirrhotic) portal hypertension. However, diagnosing NRH is challenging. The objective of this study was to determine inter- and intraobserver agreement on the histopathologic diagnosis of NRH. METHODS: Liver specimens (n=48) previously diagnosed as NRH, were reviewed for the presence of NRH by seven pathologists without prior knowledge of the original diagnosis or clinical background. The majority of the liver specimens were from thiopurine using inflammatory bowel disease patients. Histopathologic features contributing to NRH were also assessed. Criteria for NRH were modified by consensus and subsequently validated. Interobserver agreement was evaluated by using the standard kappa index. RESULTS: After review, definite NRH, inconclusive NRH and no NRH were found in 35% (23-40%), 21% (13-27%) and 44% (38-56%), respectively (median, IQR). The median interobserver agreement for NRH was poor (κ = 0.20, IQR 0.14-0.28). The intraobserver variability on NRH ranged between 14% and 71%. After modification of the criteria and exclusion of biopsies with technical shortcomings, the interobserver agreement on the diagnosis NRH was fair (κ = 0.45). CONCLUSIONS: The interobserver agreement on the histopathologic diagnosis of NRH was poor, even when assessed by well-experienced liver pathologists. Modification of the criteria of NRH based on consensus effort and exclusion of biopsies of poor quality led to a fairly increased interobserver agreement. The main conclusion of this study is that NRH is a clinicopathologic diagnosis that cannot reliably be based on histopathology alone.